Testicular-sparing surgery in the pediatric population: multicenter review of practice with review of the literature. Issue 5 (September 2019) - Radford, Anna; Peycelon, Matthieu; Haid, Bernhard; Powis, Mark; Lakshminarayanan, Bhanu
Abstract : Purpose of review: Pediatric testicular tumors have predominantly favorable histology, which may permit testicular sparing surgery (TSS). Limited guidance exists for TSS in adults and is absent in pediatric practice. The international survey and retrospective case series evaluated the current use of TSS in pediatric testicular tumors. Alongside the complementary literature review, the aim of this work was to provide evidence that could be used to produce a guideline document. Recent findings: Published evidence advocates small mass size as an indicator for TSS, this was not supported in the pediatric literature. Frozen section examination at TSS was not always performed by surgeons and yet the literature reports close to 100% specificity. Tumor markers and ultrasound findings are also used as indicators for TSS, a finding reflected in our survey results. Summary: Multiple case series are reported but no large data series exists, which will require international collaboration rather than a drive to publish the results of individual centers. Common indicators for TSS use; such as tumor markers and imaging are known but further work needs to evaluate the role of on-table histology and the risks of this not being available.